Making The Casher Application For The Tonguewing Meatball Restaurant Using Mysql And Netbeans - Adam Huda Nugraha (Publisher Cv. Inara, 2021)
The development of information technology and science in the field of automation has recently had a great influence in almost all fields. An automated system makes all work easier with very accurate results and reduces processing time. In this scientific writing, the author discusses the difficulties in the data collection process, calculating the total price and checking data in a restaurant that still uses the manual method, which is why the author creates this application that aims to simplify and facilitate entrepreneurs help build their business from mistakes or even losses that can be detrimental to both the customer and the restaurant manager. The design of this POS application uses UML, navigation structures and flowcharts. For the software, the author uses NetBeans and MySQL applications to process the database.